Breath taking : the power, fragility, and future of our extraordinary lungs - Stephen, Michael J. (Atlantic Monthly Press, 2021)
Pulmonologist Michael J. Stephen sheds light on our neglected and extraordinary lungs. He relates the history of oxygen on Earth and the evolutionary origins of breathing, and explores the healing power of breath and its spiritual potential. He explains the links our lungs have with our immune system and with society at large; offers chronicles of pulmonary research and discovery and human stories of resilience and recovery.